A signal amplification system on a lateral flow immunoassay detecting for hepatitis e‐antigen in human blood samples. Issue 7 (18th March 2019) - Si, Jinhong; Li, Jinfeng; Zhang, Ling; Zhang, Weiyun; Yao, Jinxiu; Li, Tingting; Wang, Wenjing; Zhu, Weihang; Allain, Jean‐Pierre; Fu, Yongshui; Li, Chengyao
Abstract: Hepatitis B e‐antigen (HBeAg) is the secretory form of the nucleocapsid of the hepatitis B virus (HBV), which is a marker of viral replication. In this study, a novel signal amplification system (SAS) based on the lateral flow immunoassay (LFIA) was used for rapid detection of HBeAg in blood samples from patients or blood donors. In this assay, the detection antibody was conjugated with gold nanoparticles (GNPs), and the capture antibody was labeled with biotin. The presence of targeting antigen HBeAg in blood sample would act as a bridge with biotinylated captured antibody and GNP‐conjugated detection antibody to form the dendritic nanoparticle complex. The dendritic complexes in the sample solution were migrated and immobilized on the testing line of strip coated with antibiotin antibodies. Signal intensity was massively amplified by the SAS, which was positively correlated with the concentration of targeting antigen in the blood sample and was assessed by eyes or strip scanner. The SAS worked only when targeting antigens were present in the sample. By using this SAS‐LFIA, we were able to detect a very low concentration of HBeAg (9 ng/mL), which was 27‐fold sensitive than that by conventional LFIA (cLFIA). A number of 420 blood samples were detested by this novel SAS‐LFIA, the results were in accordance with those of enzyme‐linked immunosorbent assay (ELISA) completely, while the cLFIA missed an HBeAg‐positive sample. In conclusion, the novel SAS has high specificity and sensitivity, which can be used to replace the conventional rapid test and ELISA in clinical diagnosis. Highlights: A novel signal amplification system (SAS) was designed to form the dendritic nanoparticle complex. SAS was applied in lateral flow immunoassay (LFIA). SAS‐LFIA was compared with conventional LFIA for detection of HBeAg. SAS‐LFIA has high sensitivity and specificity in testing of clinical samples.